THE LABOR MARKET OF TRADITIONAL MEDICAL PRACTITIONERS IN THE SOCIOLOGICAL PERSPECTIVE - Rohmah, Ichmi Yani Arinda (Journal of Social Political Sciences, 2024)
This article presents analytical data on labor market opportunities, especially for traditional medical practitioners and a reflection of Government Regulation Number 103 of 2014. The need to maintain physical health is the main thing for the community. Many people try to maintain their health so they don't get sick easily. There are many ways to maintain endurance, including consuming healthy food and drinks from natural ingredients, one example is herbal medicine from natural ingredients. In addition, people have a tendency to panic too much when their body health is disturbed, for example fever, flu and cough, the symptoms experienced may resemble those of being infected with covid-19, but not all of these symptoms always diagnose that they have been infected with covid-19. In the covid-19 pandemic situation, for example, there are still many people who check their health at traditional medical practitioners. The results of this study reveal that the traditional labor market for medical practitioners is still in great demand by the community, even though there has been government regulation on traditional health services.